To Assess the Influence of Hydrophilic Polymers on the Performance of Effervescent Floating Tablets of Tinidazole using 32 Full Factorial Design - Asane, Govind (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The current research was carried out to assess the influencing properties of hydrophilic polymers such as hydroxypropyl methylcellulose (HPMC) K4M and HPMC K15M on the performance parameters of effervescent floating tablets (EFT) of tinidazole such as floating lag time (FLT), total floating time (TFT), swelling index (SI) in HCl, and time taken to release 80% of the drug by applying 32full factorial design to improve the gastric residence time of the drug in the gastrointestinal tract. Method: The independent variables selected were the amount of HPMC K4M (X1) and HPMC K15M (X2) and the responses studied were FLT (Y1), TFT (Y2), Swelling Index (SI) in 0.1N HCl (Y3), and time taken to release 80% of drug (t80%) (Y4) by plotting response surface graphs and contour plots. Results: The FLT of prepared batches was in the range from 16 ± 0.02 to 45 ± 0.03 sec. and the minimum FLT was shown by OB-1 (16 sec.) batch. The TFT of all batches showed buoyancy and intactness for 12 h. The swelling in 0.1N HCl at 8 h ranged between 48.20 ± 0.02 and 54.33 ± 0.02. In vitro, drug release studies demonstrated that more than 95% of the drug was released in 12 h, whereas OB-2 took 10 h to release 80% of the drug. The response surface graphs and contour plots showed the effect of variables on responses such as FLT (Y1) which was found to be positively influenced by X2, and analysis of variance (ANOVA) for the response surface quadratic model for FLT was found to be significant (P < 0.0004). The TFT (Y2) was found to be influenced by X1 and ANOVA for the response surface quadratic model for TFT was found to be significant (P < 0.0001) whereas SI (Y3) was found to be influenced by X2 and ANOVA for response surface quadratic model for the SI was found to be significant (P < 0.0001) and time taken for 80% of drug release (t80%) (Y4) was found to be influenced by X2 and ANOVA for response surface quadratic model for the time taken to 80% drug release (t80%) was found to be significant (P < 0.0006). Conclusion: Both variables influenced the performance parameters, and HPMC K15M (X2) was more predominant in the overall performance of EFT. From all the batches, the OB-2 batch possesses ideal performance parameters and hence can be further taken for conducting in vivo studies.